Psychological well-being and its relationship to religious behavior among students of Sultan Qaboos University - Sultanate of Oman - Alabri, Hilal Salim Sulaiman (Journal of Educational and Psychological Sciences, 2023)
This study aimed to measure the psychological well-being of students of Sultan Qaboos University, Sultanate of Oman, as well as the level of religious interaction with students, as well as the same relationship between the two variables using the descriptive-relational approach. and 195 students. The Riff scale of psychological well-being was applied, where the diversity of the evidence of the validity of the arbitrators, as well as the reliability of the Cronbach alpha, was applied. The study also concluded that there were no statistically significant differences between the sexes due to any variable. The level of religious engagement The significance percentage was (0.05≥α) in the study estimates in the study sample in the climatic regions; As well as a statistical correlation between all areas of the two scales. The study concluded with a set of recommendations, which indicate the importance of working to increase awareness programs on religious methods, as well as increasing entertainment programs that target both sides, which helps to increase students’ awareness about psychological well-being issues and religious methods of dealing. It is also important to work on finding studies related to psychological well-being. and methods of religious interaction.